2021
DOI: 10.1002/ehf2.13295
|View full text |Cite
|
Sign up to set email alerts
|

Serum potassium levels provide prognostic information in symptomatic heart failure beyond traditional clinical variables

Abstract: Aims Despite of recent advances in the pharmacological treatment, heart failure (HF) maintains significant morbidity and mortality rates. While serum potassium disorders are common and associated with adverse outcomes, the exact recommended potassium level for patients with HF are not entirely established. We aimed to investigate the prognostic role of potassium levels on a cohort of patients with symptomatic chronic HF. Methods and results Patients with symptomatic chronic HF were identified at the referral t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Concerning K levels, hyperkalemia is frequent in patients with heart failure due to different reasons, like neurohormonal alterations implicated in the illness and kidney dysfunction, and is associated with a higher risk of cardiovascular complications (Rakisheva et al 2020 ). Hyperkalemia is also markedly related to poor prognosis in those patients and may influence survival (Toledo et al 2021 ). Other studies, like Jung et al ( 2022 ), reported increased Ca and P levels in heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning K levels, hyperkalemia is frequent in patients with heart failure due to different reasons, like neurohormonal alterations implicated in the illness and kidney dysfunction, and is associated with a higher risk of cardiovascular complications (Rakisheva et al 2020 ). Hyperkalemia is also markedly related to poor prognosis in those patients and may influence survival (Toledo et al 2021 ). Other studies, like Jung et al ( 2022 ), reported increased Ca and P levels in heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…Two further publications reported the relationship between the 6MWT and mortality in pediatric patients with DCM [ 39 , 47 ], of which one investigated the use of 6MWT as a prognostic marker for death [ 39 ]. Den Boer et al found that after adjusting for factors that may impact the 6MWT distance, such as age, height and weight, the percentage predicted 6MWT distance remained a significant predictor of death (or heart transplant) [ 39 , 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…One publication identified an association between 6MWT distance and MACE, with the 6MWT distance again demonstrating prognostic value ( Table 2 ) [ 47 ]. Toledo et al reported that 6MWT distance was significantly associated with subsequent cardiac events (including cardiac hospitalization, cardiac-related death or heart transplant) (HR: 0.99; 95% CI: 0.993–0.999; G 2 = 6.30; p = 0.01) in patients with either ischemic CM (ICM) or non-ischemic CM (NICM) [ 47 ]. This publication investigated the prognostic value of serum potassium levels in HF, because they are frequently associated with adverse outcomes in patients with HF.…”
Section: Resultsmentioning
confidence: 99%
“…Our results are consistent with those of recent studies on adult HF populations. Toledo et al found that potassium levels of ≥4.7 mmol/L may facilitate the identification of patients with HF at an increased risk of adverse outcomes [ 14 ]. Aldahl et al reported that the optimal potassium range for patients with chronic HF is 4.1–4.8 mmol/L, and deviations from this range are associated with increased short-term mortality risk [ 9 ].…”
Section: Discussionmentioning
confidence: 99%